COVID-19 Barriers to Care for Pregnant Patients in Prolonged Isolation - Mary E. Burgoyne; Emad A. Elsamadicy; Liviu Cojocaru; Andrea Desai (Hindawi Limited, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the agent responsible for coronavirus disease 2019 (COVID-19), continues to have a devastating impact on healthcare systems worldwide, and many questions remain unanswered. The effect of COVID-19 on the pregnant population is widely debated, and the unique risks in pregnancy have not yet been elucidated. What has been established, however, is the recommendation for healthcare workers to use personal protective equipment (PPE) for both contact and airborne precautions to prevent transmission of the pathogen-adding another barrier to care for vulnerable populations. We report a case of a young woman from Haiti during her first pregnancy, who was admitted to the antepartum service at 22 weeks of gestation with preterm premature rupture of membranes (PPROM) and remained admitted in isolation, though asymptomatic, for over six weeks due to persistent positive SARS-CoV-2 testing. Our case highlights the unique barriers to care that COVID-19 poses to antepartum patients, particularly in the setting of pregnant women with persistent positive testing.